Kinematic analysis of peak velocities in the breaststroke as a function of the timing of the kick. Manuscript and coaching applications - Ward, S. M.; Prins, J. H.; Freemyer, B. G. (Journal of Swimming Research, 2018)
The purpose of this study was to determine the effects of the timing of the Breaststroke kick on intra-cyclic velocity fluctuations. Researchers examined peak hip velocities of Breaststroke swimmers to determine any significant velocity drop-offs and magnitude of velocity regained between different kicking techniques. Subjects performed swimming trials with three different kick protocols: a conventional kick, a late kick, and a delayed late kick. Video analysis was used to analyze peak and minimum hip velocities within one Breaststroke cycle for each trial. Data was analyzed using ANOVA repeated measures analysis. Major findings of this study were that due to smaller percentages of hip velocity drop-off, greater swimming efficiency may be achieved when the kick is initiated during the insweep or early recovery arm phases and that video analysis and verbal cueing are viable tools to help swimmers improve their regular stroke technique.